UV-induced photochemistry of matrix-isolated 1-phenyl-4-allyl-tetrazolone - Frija, L. M. T. (2007)
The photochemistry and molecular structure of 1-phenyl-4-allyl-tetrazolone (PAT) was studied by FT-IR matrix isolation spectroscopy and DFT(B3LYP)/6-311++G(d,p) calculations. The spectrum of matrix-isolated PAT monomers agrees well with the sum spectrum of three conformers predicted theoretically. UV irradiation (λ > 235 nm) of matrix-isolated PAT induces three types of photofragmentation: (1) production of phenylazide and allyl-isocyanate, with phenylazide then losing N2 to yield 1-aza-1,2,4,6-cycloheptatetraene; (2) formation of phenyl-isocyanate and allylazide; (3) N2 elimination leading to formation of 1-allyl-2-phenyldiaziridin-3-one; this compound partially reacts further to form 1-allyl-1H-benzoimidazol-2(3H)-one. The observed photochemistry of the matrix-isolated PAT is distinct from the preferred photochemical fragmentation in solution, where 3,4-dihydro-3-phenylpyrimidin-2(1H)-one is produced as the primary photoproduct.